The importance of propelling and mechanical efficiencies
Implications of the study: Propelling efficiency more than mechanical efficiency influences swimming performance. Elite swimmers are able to remain more efficient at higher speeds than lesser performers. Aerobic stroking efficiency is better than anaerobic stroking efficiency. There were some significant statements contained in the chapter that require no further clarification. They are repeated or paraphrased here. 1. Swimming hard at practice to the point that technique is destroyed by fatigue is not a productive practice. This trains the body to swim inefficiently, to go slow, and NOT to energize good technique. ". . best technique must be used during every stroke cycle." (p. 79) 2. The technique of swimming in anaerobic work must be taught. To assume that what is performed at slower aerobic speeds will be transferred to faster anaerobic speeds is false. 3. When teaching technique, the insweep and finish phases should be emphasized and the duration and degree of movement in the catch phase minimized. [Technique instructions which emphasize magnified "S" shaped pulls would seem to be incorrect.] Correct technique must be maintained even during difficult sets to correctly train the neuromuscular pathways.